2008
DOI: 10.1021/jm800002y
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the Therapeutic Activity of Nanoparticle Delivered Paclitaxel by Manipulating the Hydrophobicity of Prodrug Conjugates

Abstract: A series of paclitaxel prodrugs designed for formulation in lipophilic nanoparticles are described. The hydrophobicity of paclitaxel was increased by conjugating a succession of increasingly hydrophobic lipid anchors to the drug using succinate or diglycolate cross-linkers. The prodrugs were formulated in well defined block copolymer-stabilized nanoparticles. These nanoparticles were shown to have an elimination half-life of approximately 24 h in vivo. The rate at which the prodrug was released from the nanopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
133
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(139 citation statements)
references
References 28 publications
(81 reference statements)
5
133
1
Order By: Relevance
“…Many studies have reported the reduction of PX or DX activity by conjugating fatty acid chains to 2′-OH. 21,23,24 This study is consistent with previous reports that in general, all three DX-lipid conjugates were less potent than DX against DU-145 cells, and increasing the lipid chain length decreased the cell growth inhibitory activity in vitro. It has been previously demonstrated that esterification at 2′-OH or 7-OH abolished the microtubule binding affinity of the conjugates but not the total toxicity.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…Many studies have reported the reduction of PX or DX activity by conjugating fatty acid chains to 2′-OH. 21,23,24 This study is consistent with previous reports that in general, all three DX-lipid conjugates were less potent than DX against DU-145 cells, and increasing the lipid chain length decreased the cell growth inhibitory activity in vitro. It has been previously demonstrated that esterification at 2′-OH or 7-OH abolished the microtubule binding affinity of the conjugates but not the total toxicity.…”
supporting
confidence: 92%
“…21 It has been previously reported that the conjugation of fatty acids to DX and PX occurs preferentially on 2′-OH. 21,23,24 By controlling the molar ratio of the fatty acid chloride to DX carefully, 2′-mono substituted DX conjugates were obtained with minimal formation of 2′,7-di substituted byproducts and unreacted DX. In the case of C22-DX, only the 2′-OH ester derivative was obtained after washing with 5% HCl and brine as determined by thin layer chromatography and nuclear magnetic resonance, without further chromatography required.…”
Section: Synthesis and Characterization Of DX Conjugatesmentioning
confidence: 99%
See 1 more Smart Citation
“…An estimate of the half life (t 50 ) required to reach 50% release may be obtained by replotting Figure 7 in a log-log form to extrapolate it to M t /M 1 ¼ 0.5 (figure not shown). [9] These half lives are listed in Table 2, and they range from 40 to 400 h indicating good (4 8C) storage stability. It is also clear that crosslinking the double-layer improves the stability, as reflected in both the half life and the apparent diffusivity D e in Table 2.…”
Section: Stability Of Nanocapsules and Controlled Drug Releasementioning
confidence: 99%
“…[17][18][19] Modification of PTX with fatty acid derivatives is one potential approach. It has been reported that docosahexaenoic acid-PTX is currently in Phase III clinical trials.…”
mentioning
confidence: 99%